Marker-assisted pyramiding of two major, broad-spectrum bacterial blight resistance genes, Xa21 and Xa33 into an elite maintainer line of rice, DRR17B - Balachiranjeevi, C.H.; Bhaskar Naik, S.; Abhilash Kumar V.; Harika, G.; Mahadev Swamy, H.K.; Sk, Hajira; Dilip Kumar, T.; Anila, M.; Kale, R.R.; Yugender, A.; Pranathi, K.; Koushik, M.B.V.N.; et al. (Public Library of Science, 2018)
Bacterial blight (BB) disease reduces the yield of rice varieties and hybrids considerably in many tropical rice growing countries like India. The present study highlights the development of durable BB resistance into the background of an elite maintainer of rice, DRR17B, by incorporating two major dominant genes, Xa21 and Xa33 through marker-assisted backcross breeding (MABB). Through two sets of backcrosses, the two BB resistance genes were transferred separately to DRR17B. In this process, at each stage of backcrossing, foreground selection was carried out for the target resistance genes and for non-fertility restorer alleles concerning the major fertility restorer genes Rf3 and Rf4, using gene-specific PCR-based markers, while background selection was done using a set of 61 and 64 parental polymorphic SSR markers respectively. Backcross derived lines possessing either Xa21 or Xa33 along with maximum genome recovery of DRR17B were identified at BC3F1 generation and selfed to develop BC3F2s. Plants harboring Xa21 or Xa33 in homozygous condition were identified among BC3F2s and were intercrossed with each other to combine both the genes. The intercross F1 plants (ICF1) were selfed and the intercross F2(ICF2) plants possessing both Xa21 and Xa33 in homozygous condition were identified with the help of markers. They were then advanced further by selfing until ICF4 generation. Selected ICF4 lines were evaluated for their resistance against BB with eight virulent isolates and for key agro-morphological traits. Six promising two-gene pyramiding lines of DRR17B with high level of BB resistance and agro-morphological attributes similar or superior to DRR17B with complete maintenance ability have been identified. These lines with elevated level of durable resistance may be handy tool for BB resistance breeding.